Pengaruh Kualitas Produk dan Pelayanan terhadap Kepuasan Pelanggan di Story Coffee - Olip Sagita; Iskandar Ali Alam; Nuris Sanida (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of product quality and service quality on consumer satisfaction at Story Coffee, a coffee shop located in Mesuji, Lampung. The research method used was a quantitative approach with a data collection technique through the distribution of questionnaires to 100 respondents. Data analysis was carried out using multiple linear regression through SPSS software. Product quality variables include aspects of taste, freshness, and appearance of the product, while service quality includes service speed, staff friendliness, and café atmosphere. The results of the study show that both product quality and service quality have a positive and significant influence on consumer satisfaction. These findings indicate that consistently improving product and service quality standards can improve customer satisfaction, which in turn contributes to consumer loyalty and business sustainability. In addition, there are other factors outside of the variables studied that also affect the level of consumer satisfaction. This study recommends that Story Coffee management continue to evaluate and improve the quality elements of products and services in order to maintain competitiveness and strengthen long-term relationships with customers.